Melanoma da coróide na criança - Relato de caso e revisão da literatura - Schellini, Silvana Artioli (1996)
The uveal melanoma is unusual in children. We described a child five years old with choroidal melanoma with occurred with low vision, red eye and ocular pain. The ultrassonographic an tomographic exams showed large intraocular tumor and in the histopathological analysis we founded epithelioid melanoma of small cells. Prognostic factors and the rarity of the uveal melanoma in the children were emphasised.